2013
DOI: 10.5194/acp-13-12573-2013
|View full text |Cite
|
Sign up to set email alerts
|

Size-resolved atmospheric particulate polysaccharides in the high summer Arctic

Abstract: Abstract. Size-resolved aerosol samples for subsequent quantitative determination of polymer sugars (polysaccharides) after hydrolysis to their subunit monomers (monosaccharides) were collected in surface air over the central Arctic Ocean during the biologically most active summer period. The analysis was carried out by novel use of liquid chromatography coupled with highly selective and sensitive tandem mass spectrometry. Polysaccharides were detected in particle sizes ranging from 0.035 to 10 µm in diameter … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
74
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(86 citation statements)
references
References 70 publications
(92 reference statements)
12
74
0
Order By: Relevance
“…For the former case, this may involve both direct emissions of larger polymer gel accumulation-mode particles and the growth of smaller particles via two processes, namely heterogeneous condensation and aerosol cloud processing in which the bimodal particle size distribution characteristic of cloud-processed air is created (Hoppel et al, 1994). Previous studies in the same area and season (Heintzenberg et al, 2006;Chang et al, 2011;Heintzenberg and Leck, 2012;Kupiszewski et al, 2013;Hellén et al, 2012;Nilsson and Leck, 2002;Leck et al, 2013;Leck and Persson, 1996b;Leck and Bigg, 2005) have shown raised concentrations of accumulation-mode particles within the high Arctic boundary layer which the authors attribute to sources upwind Oden: transport of precursor gases and marine biogenic particles from the MIZ or locally from open leads over the pack ice. Previously reported results of individual particles by Leck (2001, 2008), Leck et al (2002), and Bigg (2005a, b, 2010) collected over the pack ice however have failed to find evidence of sea salt particles of less than 200 nm in diameter.…”
Section: Synopsis and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…For the former case, this may involve both direct emissions of larger polymer gel accumulation-mode particles and the growth of smaller particles via two processes, namely heterogeneous condensation and aerosol cloud processing in which the bimodal particle size distribution characteristic of cloud-processed air is created (Hoppel et al, 1994). Previous studies in the same area and season (Heintzenberg et al, 2006;Chang et al, 2011;Heintzenberg and Leck, 2012;Kupiszewski et al, 2013;Hellén et al, 2012;Nilsson and Leck, 2002;Leck et al, 2013;Leck and Persson, 1996b;Leck and Bigg, 2005) have shown raised concentrations of accumulation-mode particles within the high Arctic boundary layer which the authors attribute to sources upwind Oden: transport of precursor gases and marine biogenic particles from the MIZ or locally from open leads over the pack ice. Previously reported results of individual particles by Leck (2001, 2008), Leck et al (2002), and Bigg (2005a, b, 2010) collected over the pack ice however have failed to find evidence of sea salt particles of less than 200 nm in diameter.…”
Section: Synopsis and Conclusionmentioning
confidence: 99%
“…The colors correspond to those in Fig. 13. ings includes the fact that near-surface airborne aerosol, as well as low-level cloud and fog droplets, contained the same type of polymer gel material as found in the open-lead surface microlayer (Gao et al, 2012;Leck et al, 2013;Orellana et al, 2011;Bigg et al, 2004;Leck and Bigg, 2005).…”
Section: Synopsis and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…S5). The additional occurrence of glucose in the coarse particles (>1 mm) may be due to degradation of polysaccharides occurred during long range transport processes (Leck et al, 2013). Biological degradation, as a source of sugars, is also indicated by the higher mean concentration of sucrose (96 pg m À3 ) in the 2014e2015 samples compared to the mean concentration (3 pg m À3 ) in the 2010e2011 samples (Barbaro et al, 2015a).…”
Section: Sugars In Pm 10mentioning
confidence: 88%